2011
DOI: 10.1093/ndt/gfr057
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity is the most significant metabolic syndrome component predictive of cardiovascular events in chronic hemodialysis patients

Abstract: IDF-defined MetS was more predictive of CVEs than AHA/NHLBI-defined MetS. Of the MetS components, abdominal obesity was the single most significant predictor of CVEs in chronic HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
1
31
1
Order By: Relevance
“…Hypertension has been described as one of the most important factors for the development of metabolic syndrome,27,29–31 together with central obesity 27,30,31. However, the criteria for central obesity also differed among the various studies, some of which measured it according to waist circumference while others used the body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension has been described as one of the most important factors for the development of metabolic syndrome,27,29–31 together with central obesity 27,30,31. However, the criteria for central obesity also differed among the various studies, some of which measured it according to waist circumference while others used the body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, even though central obesity measured as waist circumference was the third most frequent metabolic syndrome defining risk factor in patients on hemodialysis, obesity measurement according to the body mass index only accounted for 11.8% of patients. The magnitude of influence of other metabolic syndrome defining risk factors in patients on hemodialysis has not yet been fully clarified, as variable information has been reported by the different studies carried out28,29,31 depending on the criteria used for the diagnosis of metabolic syndrome 30…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in adults with mean GFR 87 ml/min/1.73 m 2 the prevalence of MS was 1 to 35 % across the same ranges of BMI [54]. Wu et al found MS in 50.5 % of dialyzed adults when the ATP III definition was used, and in 30.8 % when the IDF definition was used [55]. As in the general population, MS significantly increases CV risk in adults with CKD and even in dialyzed patients.…”
Section: The Prevalence Of Metabolic Abnormalities and Metabolic Syndmentioning
confidence: 99%
“…The accumulation of abdominal fat increases waist size. Several studies have suggested that abdominal obesity is associated with type 2 diabetes (Heianza et al, 2014), cardiovascular disease (Shields et al, 2012), and metabolic syndrome (Wu et al, 2011). Furthermore, the Canadian Health Measures Survey found a positive association between abdominal obesity and cardiovascular disease among men and women with normal BMI (Shields et al, 2012).…”
Section: Introductionmentioning
confidence: 99%